A modeling approach to estimating N2O emission derived from loss of soil organic matter for the Japanese greenhouse gas inventory. Issue 3 (4th May 2021) - Shirato, Yasuhito; Kishimoto-Mo, Ayaka W.; Takata, Yusuke
ABSTRACT: We designed a new approach for modeling the nitrous oxide (N2 O) derived from nitrogen (N) mineralization associated with loss of soil organic matter (SOM) that meets the current IPCC guidelines (GL) because the method currently used in the National GHG Inventory Report (NIR) of Japan does not. Loss of soil carbon (C) was calculated by using the previously developed nationwide soil C calculation system for agricultural soils. We conducted a zero-C-input soil C modeling experiment, which is a one-year simulation without C input after a long-term 'normal' simulation with C input. Because no new organic matter was added to the system in the one-year simulation, we considered that C loss was equal to the C loss from SOM loss. Next, the amount of C loss was divided by the soil C/N ratio for each soil and agricultural land use type to calculate the amount of N mineralization. Finally, N mineralization quantity was converted to N2 O emission by using an empirical model. Because the use of this empirical model cannot be justified for paddy fields, the use of IPCC default emission factor should be recommended instead of the empirical model-derived emission. We consider that these calculated N2 O is derived from N mineralization associated with SOM loss. Our new approach, however, was not yet validated against field observation. The results are therefore only tentative and waiting for the field validation.